Implementasi Pendaftaran Tanah Sistematis Lengkap (PTSL) sebagai Perwujudan Kebijakan Publik di Kota Surabaya - Nadian, Ussy; Tukiman, Tukiman (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The Complete Systematic Land Registration Program (PTSL) aims to accelerate the process of registering land parcels throughout the territory of the Republic of Indonesia. This is also applied by Dr. Kelurahan. Soetomo City of Surabaya. The purpose of this research is to explore the implementation of the PTSL policy in Dr. Soetomo City of Surabaya, taking into account the theory of public policy implementation according to George C. Edward III, there are 4 (four) indicators, namely communication, resources, dispositions, and bureaucratic structure. This research method is to apply a type of qualitative approach. Data comes from both primary and secondary. Data collection was carried out by interviews, observation, documentation, and data trackingonline. Data analysis was carried out using reduction, triangulation, and concluding as well as verification methods. The results of the study show that communication in the PTSL program has not been realized properly, as a result of the socialization delivery that has not been maximized. The resources in the PTSL program have been maximally realized, starting from people, budget, as well as facilities and infrastructure. Disposition has also been maximized, with good employee attitudes. The bureaucratic structure is good with a neat flow, but it is not strong enough because some employees are not placed according to their expertise. Implementation of PTSL policy in Kelurahan Dr. Soetomo City of Surabaya has thus been implemented well, but not optimally. due to communication factors and bureaucratic structures that are not running according to goals and plans.